간경변의 진단. - 서연석 (Journal of the Korean Medical Association / Taehan Uisa Hyophoe Chi, 2017)
Liver cirrhosis results from chronic liver injury that leads to necroinflammation and fibrosis. The development of liver cirrhosis is significantly associated with increased morbidity and mortality. Liver biopsy has been considered to be the gold standard for the diagnosis of liver cirrhosis, which is characterized by diffuse fibrosis and the development of regenerating nodules. However, liver biopsy is invasive and has some drawbacks, such as sampling error and intraobserver and interobserver variability in the assessment of fibrosis stages. Recently, various non-invasive tests such as serum markers, radiologic tests, and elastography have been investigated to overcome the limitations of liver biopsy. This review will focus on the use of these non-invasive tests for diagnosing liver cirrhosis.